2020
DOI: 10.3389/frai.2020.00039
|View full text |Cite
|
Sign up to set email alerts
|

A New Acoustic-Based Pronunciation Distance Measure

Abstract: We present an acoustic distance measure for comparing pronunciations, and apply the measure to assess foreign accent strength in American-English by comparing speech of non-native American-English speakers to a collection of native American-English speakers. An acoustic-only measure is valuable as it does not require the time-consuming and error-prone process of phonetically transcribing speech samples which is necessary for current edit distance-based approaches. We minimize speaker variability in the data se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 62 publications
1
26
0
1
Order By: Relevance
“…Additionally, finegrained pronunciation differences that are relevant for studying accented speech may not be captured by using a set of discrete symbols (Mermelstein, 1976;Duckworth et al, 1990;Cucchiarini, 1996). Bartelds et al (2020) therefore introduced an acoustic-only measure for comparing pronuncia-tions. In their method, they represented accented speech as 39-dimensional Mel-frequency cepstral coefficients (MFCCs), which were used to compute acoustic-based non-native-likeness ratings between non-native and native speakers of English.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, finegrained pronunciation differences that are relevant for studying accented speech may not be captured by using a set of discrete symbols (Mermelstein, 1976;Duckworth et al, 1990;Cucchiarini, 1996). Bartelds et al (2020) therefore introduced an acoustic-only measure for comparing pronuncia-tions. In their method, they represented accented speech as 39-dimensional Mel-frequency cepstral coefficients (MFCCs), which were used to compute acoustic-based non-native-likeness ratings between non-native and native speakers of English.…”
Section: Introductionmentioning
confidence: 99%
“…This result was close to, but still not equal to the performance of a phonetic transcriptionbased approach (which showed a correlation of r = −0.77). Bartelds et al (2020) also conducted several small-scale experiments to investigate whether more fine-grained characteristics of human speech were captured compared to the phonetic transcription-based pronunciation difference measure. Their results showed that the acousticonly measure captured segmental differences, intonational differences, and durational differences, but that the method was not invariant to characteristics of the recording device.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations